Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1210/endo.132.2.8425481
|View full text |Cite
|
Sign up to set email alerts
|

Rat liver 11 beta-hydroxysteroid dehydrogenase complementary deoxyribonucleic acid encodes oxoreductase activity in a mineralocorticoid-responsive toad bladder cell line.

Abstract: The mineralocorticoid receptor displays equal affinity for aldosterone and corticosterone. It has been proposed that aldosterone selectivity in vivo is achieved by the conversion of corticosterone into its inactive metabolite 11-dehydrocorticosterone by 11 beta-hydroxysteroid dehydrogenase (11 beta HSD). To test this hypothesis, we transfected rat liver 11 beta HSD cDNA into TBM cells, a sodium-transporting cell line. These cells respond equally well to aldosterone and corticosterone, indicating that endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…These results conform with most previous studies of 11 -HSD-1 in intact cells (Duperrex et al 1993, Low et al 1994, Hundertmark et al 1995, Jamieson et al 1995, Rajan et al 1996, and more recently, with the predominant reaction direction in whole organs and in vivo (Kotelevtsev et al 1997). However, Monder et al (1994a) found significant 11 -dehydrogenation in rat Leydig cells, although reductase activity was not determined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results conform with most previous studies of 11 -HSD-1 in intact cells (Duperrex et al 1993, Low et al 1994, Hundertmark et al 1995, Jamieson et al 1995, Rajan et al 1996, and more recently, with the predominant reaction direction in whole organs and in vivo (Kotelevtsev et al 1997). However, Monder et al (1994a) found significant 11 -dehydrogenation in rat Leydig cells, although reductase activity was not determined.…”
Section: Discussionsupporting
confidence: 91%
“…11 -Reductase predominance is seen in most transfected cells (Duperrex et al 1993, Low et al 1994 and in primary cultures of rat hepatocytes ( Jamieson et al 1995), lung cells (Hundertmark et al 1995), neurons (Rajan et al 1996), vascular smooth muscle cells (Brem et al 1995) and human adipose cells (Bujalska et al 1997). Moreover, 11 -HSD-1 reductase appears functionally important, since it amplifies glucocorticoid action via glucocorticoid receptors (GR) in transfected cells (Low et al 1994) and primary cultures (Hundertmark et al 1995, Rajan et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Some suggested it might be a lower affinity 11␤-dehydrogenase. However, studies in clonal amphibian and mammalian cells transfected with rat 11␤-HSD1 cDNA showed that, whilst bidirectional in homogenates, surprisingly it acts as a predominant 11␤-reductase in most intact cells and thus functionally amplifies glucocorticoid action (174,420). Indeed, in cells expressing 11␤-HSD1, cortisone (or 11dehydrocorticosterone) is equipotent with or even more potent than cortisol (or corticosterone) (206,231,646).…”
Section: ) (Figure 2)mentioning
confidence: 99%
“…It is widely distributed, with high expression in several organs including the liver. Although 11 -HSD-1 shows bi-directional activity in tissue homogenates and purified microsomal fractions in vitro (Lakshmi & Monder 1988), near exclusive 11 -reduction has been demonstrated in both intact cells transfected with 11 -HSD-1 cDNA (Duperrex et al 1993) and primary cells in culture, including hepatocytes ( Jamieson et al 1995).…”
Section: Introductionmentioning
confidence: 99%